Screening of antibiotic resistance genes in pathogenic bacteria isolated from tiny freshwater shrimp (Macrobrachium lanchesteri) and “Kung Ten”, the uncooked Thai food - Thongkao, Kanittada; Sudjaroen, Yuttana (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to isolate and identify of pathogenic bacteria in tiny freshwater shrimp (Macrobrachium lanchesteri) and in Kung Ten, which is an unusual Thai cuisine that eaten alive shrimp directly. Antimicrobial susceptibility test and identification of antibiotic resistance genes for isolated bacteria were conducted. Materials and Methods: Eighty of fresh shrimp samples and forty of Kung Ten salads were collected from four fresh markets, which were located in Bangkok and Nonthaburi province (N = 120). The isolation, identification, and antimicrobial susceptibility test of pathogenic bacteria were done following the Clinical and Laboratory Standards Institute guidelines. Antibiotic-resistant bacteria were screened for β-lactamase relating genes, such as AmpC (MOX and ACC genes), blaCTX-M, and Int1 genes. Results: The number of bacterial isolates in tiny freshwater shrimp and Kung Ten salad was 136 and 65, respectively. Aeromonas caviae, A. hydrophilla, Proteus penneri, Proteus vulgaris, and Klebsiella pneumoniae were commonly found. Ampicillin, amoxicillin/clavulanic, cefuroxime, tetracycline, and trimethoprim/sulfamethoxazole resistance were observed, and common antibiotic-resistant bacteria were A. caviae, P. vulgaris, Enterobacter Aerogenes, and K. pneumoniae. A. caviae, P. penneri, K. Pneumoniae, and A. hydrophilla were positive for MOX gene; blaCTX-M, and Int1 genes; ACC and Int1 genes; and ACC gene, respectively. Conclusion: Raw or uncooked shrimps in Kung Ten salad may a risk in foodborne diseases due to positive for pathogenic bacterial isolates. However, hygienic control on food preparation is difficult to apply because of the difficulty of changing in local Thai food behavior. J. Adv. Vet. Anim. Res., 7(1): 83-91, March 2020